UNSUR INTRINSIK DALAM NOVEL GITNJALI KARYA FEBRIALDI R. BERDASARKAN TEORI STRUKTURAL ROBERT STANTON - Nengsih, Riska Ayu; Rapi, Muhammad; Juanda, Juanda (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2020)
This study aims to describe the intrinsic elements in the Gitanjali Karya Febrialdi R novel based on Robert Stanton's structural theory. The data generated in the form of descriptive data. This research data is written data in the form of words, expressions, and sentences. There are two data sources, namely primary data and secondary data. There are two data collection techniques, namely the reading technique and the note taking technique. The results showed that the theme contained in the novel is the struggle and offerings of love. There are facts of the story which are divided into three, namely the plot, character and setting, and literary tools that produce the title, point of view, language style, tone, and symbolism.